An Economist's Guide to Digital Music - Martin Peitz; Patrick Waelbroeck (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
In this guide, we discuss the impact of digitalization on the music industry. We rely on market and survey data at the international level as well as expert statements from the industry. The guide investigates recent developments in legal and technological protection of digital music and describes new business models as well as consumers' attitude towards music downloads. We conclude the guide by a discussion of the evolution of the music industry.
urn:nbn:de:bvb:19-epub-13516-5
Keywords: 330; Music; Internet; File-sharing; Peer-to-peer; Piracy; Digital Rights Management; Copyright; E-commerce